Response of R.C. plates under blast loading using FEM-SPH coupled method. (July 2021) - Karmakar, Somnath; Shaw, Amit
Highlights: FEM and SPH are coupled to study response of R. C. Slab under blast loading. As simulation progresses distorted elements are transformed to SPH particles. Performances of different computational idealizations are investigated. Effects of standoff distance and boundary conditions are investigated. Abstract: Response of reinforced concrete (R.C.) plates subjected to blast loading is numerically investigated through a hybrid discretization combining FEM and smoothed particle hydrodynamics (SPH). Initially, the structure is discretized via Lagrangian finite elements. If any element undergoes large deformation, it is replaced by particles. Interaction between FEM and SPH is established through a transition layer. Three different idealizations of the actual blast event involving multiphase continuum (explosive, air and structure) is considered, viz. Load Blast Enhanced (LBE) where only the structure is modeled and empirically calculated blast pressure is applied to the structure; Multi-Material Arbitrary Lagrangian Eulerian (MM_ALE) where the explosive, air and structure all are explicitly modeled; and coupled LBE & MM_ALE where the structure is encapsulated in a receptor and blast pressure is applied on the receptor. Simulations are performed to investigate the effects of various parameters such as standoff distance, boundary conditions etc., on the overall response of the structure.